PENGGUNAAN COBIT SEBAGAI FRAMEWORK MANAJEMEN RISIKO TI DI SEKTOR ASURANSI : PENDEKATAN SYSTEMATIC LITERATURE REVIEW - Nurbojatmiko; Annisa Ramadhanti (Program Studi Sistem Informasi, Universitas Banten Jaya, 2025)
This study aims to examine the impact of implementing the COBIT (Control Objectives for Information and Related Technology) framework on IT governance in various organizations, based on a review of relevant literature. COBIT is recognized as a comprehensive framework for effective IT governance and management. Based on the analysis of several recent scholarly publications, it is evident that the implementation of COBIT consistently leads to positive outcomes, including improved operational efficiency, enhanced IT risk control, better regulatory compliance, and higher quality of IT services. Additionally, COBIT supports organizations in identifying performance gaps and aligning IT strategies with business goals. These findings reinforce the core idea of this research—that COBIT serves as a strategic and effective tool for structured and sustainable IT governance. Therefore, the adoption of COBIT not only enhances a company’s IT capabilities but also provides added value in managerial decision-making through risk-based control mechanisms.